2005
DOI: 10.1542/peds.2004-0067
|View full text |Cite
|
Sign up to set email alerts
|

Asthma-Related Health Care Resource Use Among Asthmatic Children With and Without Concomitant Allergic Rhinitis

Abstract: Children with comorbid allergic rhinitis incurred greater prescription drug costs and experienced more GP visits and hospitalizations for asthma than did children with asthma alone. A unified treatment strategy for asthma and allergic rhinitis, as recommended by the Allergic Rhinitis and Its Impact on Asthma initiative, might reduce the costs of treating these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
1
15

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(109 citation statements)
references
References 28 publications
4
89
1
15
Order By: Relevance
“…Retrospective studies also point towards the same data. During 1998-2001, a UK cohort study involving general practitioner medical records of 6-to 15-year-olds showed that 19.7 % of the asthmatic patients had AR [15]. Similarly, in the Norway National Database, 26.8 % of the children with at least one hospital admission for asthma, over a 2-year period, had a documented history of AR [16].…”
Section: Epidemiologic Evidencementioning
confidence: 99%
“…Retrospective studies also point towards the same data. During 1998-2001, a UK cohort study involving general practitioner medical records of 6-to 15-year-olds showed that 19.7 % of the asthmatic patients had AR [15]. Similarly, in the Norway National Database, 26.8 % of the children with at least one hospital admission for asthma, over a 2-year period, had a documented history of AR [16].…”
Section: Epidemiologic Evidencementioning
confidence: 99%
“…A coexistência de rinite como um marcador de gravidade para a asma tem sido relatada por outros autores, que registraram também maior dificuldade no controle desta última, e custos mais elevados com o tratamento quando as duas condições encontram-se associadas 11,12,13 . Os dados aqui obtidos foram semelhantes àqueles registrados em São Paulo, em estudo ISAAC que evidenciou freqüência significativamente maior de relato de "quatro ou mais crises de sibilos no último ano", "distúrbio do sono devido a sibilos", "crises de sibilos limitando a fala" e "broncoespasmo induzido por exercício" entre adolescentes com a comorbidade asma-rinite, em relação àqueles com asma, mas sem rinite 36 .…”
Section: Discussionunclassified
“…Estudos epidemiológicos, envolvendo principalmente pacientes acompanhados em ambulatórios, têm registrado altas prevalências de rinite entre pacientes asmáticos 9,10 . Pesquisas têm demonstrado também que os pacientes com essa comorbidade têm apresentado manifestações mais graves de asma, resultando em maior número de visitas aos serviços de emergências e de hospitalizações quando comparados àqueles com asma sem rinite, e acarretando maior comprometimento da qualidade de vida e maior custo com o tratamento dos asmá-ticos 11,12,13 .…”
Section: Introductionunclassified
“…85,101 In atopic children, the presence of allergic rhinitis is a risk factor for asthma, with a time interval of about a year before the development of asthma symptoms, 102 offering a potential window of opportunity when early detection and appropriate management of rhinitis may prevent the progression to asthma. Co-morbid rhinitis is associated with increased asthma symptoms, increased exacerbations and hospital admissions, [103][104][105] with some evidence that concomitant treatment can improve control. 106,107 Research questions:…”
Section: Rhinitis and Asthmamentioning
confidence: 99%